Community health centers at the crossroads: Growth and staffing needs. Issue 4 (April 2015) - Proser, Michelle; Bysshe, Tyler; Weaver, Donald; Yee, Ronald
Abstract : Abstract: In response to increased demand for primary care services under the Affordable Care Act, the national network of community health centers (CHCs) will play an increasingly prominent role. CHCs have a broad staffing model that includes extensive use of physician assistants (PAs), nurse practitioners (NPs), and certified nurse midwives (CNMs). Between 2007 and 2012, the number of PAs, NPs, and CNMs at CHCs increased by 61%, compared with 31% for physicians. However, several policy and payment issues jeopardize CHCs' ability to expand their workforce and meet the current and rising demand for care.